Design of A Dekstop-Based Chronological Form Information System to Improve BPJS Claims Using The Waterfall Method - Putri Aprilia Kartika; Falaah Abdussalaam; Sali Setiatin (Greenation Research & Yayasan Global Resarch National, 2026)
Implementing information system technology in hospitals is a crucial step toward making work faster and more accurate. The chronological form is a medical record document used to record—in detail—the time, location, and description of incidents affecting a patient prior to or during their care in the Emergency Department (ED). This document is typically used for accident and trauma cases or for patients covered by BPJS (Social Security Agency on Health). Currently, these forms are filled out manually on paper, creating a risk of delays and recording errors. This study aims to design a chronological form information system for the BPJS claims process to enhance staff performance effectiveness. The Waterfall method was employed as the software development approach. Data collection involved interviews, observations, and a review of existing paper-based chronological forms. The system was developed using Microsoft Visual Studio 2012 for programming and Microsoft Access for the database. The results indicate that the development of a computerized chronological form application is expected to reduce delays, minimize recording errors, and increase staff work speed. With this system in place, staff should be able to complete chronological forms more quickly and accurately.